Factor that influences credit card practices among private sector’s workers / Nurasyikin Azman and Nur Hami Farika Mohd Zaduin - Azman, Nurasyikin; Mohd Zaduin, Nur Hami Farika (Faculty of Business and Management, 2014)
The purpose of this study is to determine the significant factor that influences credit card practices among private sector’s workers in two companies which are Strateq Group and Sime Darby Plantation Sdn Bhd. The variables consist of attitude, financial knowledge and financial management as independent variables, while credit card practices as the dependent variable for this study. The respondents were 150 employees from both companies. The finding showed that attitude give influences to the credit card practices among private sector’s workers. Attitude has a positive relationship towards the credit card practices. The other two variables; financial knowledge and financial management also have a positive relationship towards the credit card practices. However, attitude is more significant and the beta is higher than other two variables. This study refers to primary data and also secondary data to supporting the sampling technique. Meanwhile, the researchers use questionnaire as the method to collect all the data from sample respondents in accomplishing the research objectives. While the data for this study was analyzed using multiple statistical procedures. The result of the study presented in this research agrees that attitude influencing the credit card practices among private sector’s workers in Strateq Group and Sime Darby Plantation Sdn Bhd.